2009
DOI: 10.12944/cwe.4.1.18
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Reproductive Behaviour of Indian Black Buck (Antilope cervicapra) Linn. with Reference to Courtship, Breeding, Fawning and Colouration

Abstract: These species exhibits a high degree of sexual dimorphism; the male is larger than the female, is strikingly coloured in black and white, and sports a magnificent pair of spiralling horns. The black of the male is replaced by an inconspicuous brown in the female. The aggressive behaviour is commonly seen throughout the year. The reproductive behaviour of black buck was recorded during the present study. The mating was primarily observed in the months of March and October. The young ones yellowish fawn in colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Vats and Bhardwaj [25] observed that the strongest individual dominated other members of the group. e encounters happened when one male entered the territory of…”
Section: Mating Behavior and Its Seasonality In Blackbuckmentioning
confidence: 99%
“…Vats and Bhardwaj [25] observed that the strongest individual dominated other members of the group. e encounters happened when one male entered the territory of…”
Section: Mating Behavior and Its Seasonality In Blackbuckmentioning
confidence: 99%
“…For example, males and females often allocate resources differently during the mating and reproductive seasons (e.g., Clutton-Brock 1989;Edelman and Koprowski 2006;Hoffman et al 2008). Indeed, male mammals spend most of their reproductive resources on mating effort and mate attraction (e.g., displays: Vats and Bhardwaj 2009; secondary sexual characteristics: Yamaguchi et al 2004), territoriality (reviewed by Clutton-Brock 1989), and male-male competition and mate defense (e.g., Wirtz 1982). In contrast, most female mammals invest less time and effort in mate selection and instead expend most of their repro-ductive effort in the production and care of offspring (Hoffman et al 2008).…”
Section: Introductionmentioning
confidence: 99%